210 Investigation of the Functional Role of the Lead Variant at the ZC3HC1 Coronary Artery Disease Locus in Cell Cycle Regulation using a Genome Editing Approach. (6th June 2015) - Jones, Pete; Kaiser, Mike; Najafabadi, Maryam Ghaderi; Webb, Tom; Samani, Nilesh
Abstract : Genome wide association studies have identified 46 chromosomal loci that are associated with coronary artery disease (CAD); however, for most of these loci the mechanism by which they affect CAD risk is unclear. The association signal at chromosome 7q32.2 is rare amongst CAD GWAS loci as the lead variant, rs11556924, introduces a coding change (His363Arg) in the ZC3HC1 gene. No other variants are in strong linkage disequilibrium, suggesting that this is the functional SNP. During interphase, ZC3HC1 promotes degradation of Cyclin B1, keeping its levels low. Inactivation of ZC3HC1 and subsequent accumulation of Cyclin B1 triggers entry into mitosis. We hypothesised that the effect of the SNP perturbs the function of ZC3HC1 in regulating the cell cycle. To investigate this, we used recombinant adeno-associated virus mediated genome editing to generate isogenic DLD-1 cell lines that are identical apart from at rs11556924. A proliferation assay comparing the rate of growth of cells of the homozygous non-risk and homozygous risk isogenic lines showed no alteration in the rate of growth of cells of different genotypes (p = 0.34). Counter-intuitively, cells carrying the risk allele showed an increase in mitotic index, with µ = 5.5% (S. E. = 0.26%) compared to µ = 3.62% (S. E. = 0.31%) in homozygote non-risk cells (p = 0.009). We tested for errors in chromosome segregation by counting the number of chromosomes in cells carrying the risk allele compared to those which are homozygous for the non-risk allele but found no difference in chromosome number (p = 0.78). In order to investigate the cause of the increase in mitotic index, we compared the time taken to complete mitosis in these cells and found that cells with the homozygote risk genotype took longer to complete mitosis with µ = 35.4 mins (S. E. = 1.08) compared to µ = 32.0 mins (S. E. = 0.88) in the homozygote non-risk cells (p = 0.01). We also compared the levels of cyclin B1 in these cells and found an increase in the levels of cyclin B1 in homozygote risk cells compared to non-risk genotype cells (p = 0.04), suggesting the SNP is perturbing the function of ZC3HC1 in promoting degradation of Cyclin B1. These data suggest that the CAD risk allele of rs11556924 perturbs Cyclin B1 dynamics causing a delay in the progression of mitosis. The mechanism by which this increases CAD risk requires further elucidation.